Improving engineering students’ understanding of classical physics through visuo-haptic simulations - González-Mena, Guillermo; Lozada-Flores, Octavio; Murrieta Caballero, Dione; Noguez, Julieta; Escobar-Castillejos, David (Frontiers in Robotics and AI, 2024)
Introduction: The teaching process plays a crucial role in the training of professionals. Traditional classroom-based teaching methods, while foundational, often struggle to effectively motivate students. The integration of interactive learning experiences, such as visuo-haptic simulators, presents an opportunity to enhance both student engagement and comprehension. Methods: In this study, three simulators were developed to explore the impact of visuo-haptic simulations on engineering students’ engagement and their perceptions of learning basic physics concepts. The study used an adapted end-user computing satisfaction questionnaire to assess students’ experiences and perceptions of the simulators’ usability and its utility in learning. Results: Feedback from participants suggests a positive reception towards the use of visuo-haptic simulators, highlighting their usefulness in improving the understanding of complex physics principles. Discussion: Results suggest that incorporating visuo-haptic simulations into educational contexts may offer significant benefits, particularly in STEM courses, where traditional methods may be limited. The positive responses from participants underscore the potential of computer simulations to innovate pedagogical strategies. Future research will focus on assessing the effectiveness of these simulators in enhancing students’ learning and understanding of these concepts in higher-education physics courses.